Monodispersed CuCo Nanoparticles Supported on Diamine‐Functionalized Graphene as a Non‐noble Metal Catalyst for Hydrolytic Dehydrogenation of Ammonia Borane. Issue 10 (19th August 2016) - Song, Fu‐Zhan; Zhu, Qi‐Long; Yang, Xin‐Chun; Xu, Qiang
Abstract: Monodispersed non‐noble CuCo nanoparticles (diameter≤2.4 nm) have been immobilized on diamine‐functionalized reduced graphene oxide, which displays remarkably enhanced catalytic performance for the dehydrogenation of ammonia borane (AB) with a corresponding turnover frequency (TOF) as high as 51.5±3.7 molH2  molcat −1  min −1 at 303 K, compared to those on other supports such as reduced graphene oxide, Vulcan XC‐72R and polyvinypyrrolidone. The synergic effect between Cu and Co could efficiently improve the catalytic performance for the hydrolytic dehydrogenation of AB. In addition, it represents a new opportunity to support various non‐noble metal nanoparticles on reduced graphene oxide, which has tremendous application prospect for various catalytic reactions. Abstract : Monodispersed non‐noble CuCo nanoparticles (diameter≤2.4 nm) have been immobilized on diamine‐functionalized reduced graphene oxide, which shows remarkably enhanced catalytic performance for the hydrolytic dehydrogenation of ammonia borane (AB) with a corresponding turnover frequency (TOF) as high as 51.5 molH2  molcat −1  min −1 at 303 K.